Libertad, religión y laicidad en materia electoral: ponderaciones comparadas - Contipelli, Ernani (Revista de Derecho, 2019)
This article aims to present the influence of the value of freedom in defining ofthe secular state, establishing its relationship with the political-electoral rights. From this perspective of view, we intend to discuss religious freedom and its mutationprocess in line with the equality and dignity of the hum an person, to verifyits correspondence with reality of the social-axiology. And, finally, to establish acomparison of the Brazilian constitutional practice regarding state secularism andreligious freedom with the constitutional provisions contained in the Mexicanlegal system.
Keywords: religious freedom; secular state; political-electoral rights